Isolated Familial Plasminogen Deficiency May not Be a Risk Factor for Thrombosis - Tait, R C; Walker, Isobel D; Conkie, J A; Islam, S I A M; McCall, Frances (Thrombosis and Haemostasis, 1996)
Despite many reports of individuals with congenital plasminogen deficiency and thrombosis, there is still uncertainty whether heterozygous deficiency represents a real thrombophilic risk factor or simply a coincidental finding. We have addressed this issue by testing for plasminogen deficiency in a cohort of 9611 blood donors. Out of 66 donors with reduced plasminogen activity on two occasions 28 were shown to have a familial deficiency state (including 3 with dysplasminogen-aemia). Our observed prevalence rate for familial plasminogen deficiency, calculated at 2.9/1000 (95% Cl = 1.9-4.2 per 1000), was not significantly different from that calculated from published reports of congenital plasminogen deficiency in thrombotic cohorts (5.4/1000). Furthermore, with only two exceptions, all 80 donors and relatives with familial deficiency were asymptomatic with regard to thrombosis -including a 29 year old donor with suspected compound heterozygous hypoplasminogenaemia. These findings add further weight to the argument that familial heterozygous plasminogen deficiency, at least in isolation, does not constitute a significant thrombotic risk factor. However, it remains uncertain whether plasminogen deficiency, when combined with other thrombophilic conditions, may become more clinically important.